How (and why) to think that the brain is literally a computer - Maley, Corey J. (Frontiers in Computer Science, 2022)
The relationship between brains and computers is often taken to be merely metaphorical. However, genuine computation can be implemented in virtually any media; thus, one can take seriously the view that brains literally compute. But without empirical criteria for what makes a physical system compute, computation may be a matter of perspective, especially for natural systems (e.g., brains) that were not explicitly designed and engineered to be computers. Considerations from real examples of physical computers—both analog and digital, contemporary and historical—make clear what those criteria are. Finally, applying those criteria to the brain shows how we can view the brain as an analog computer, and how that claim is both informative and falsifiable.